Bone marrow transplantation in the treatment of patients with acute leukemia: integrative literature review (Research, Society and Development, 2022)
Objective: To know the scientific productions on the treatment of bone marrow transplantation for patients with acute myeloid leukemia. Methodology: This is an integrative literature review carried out through the databases Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Database in Nursing (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using the following Health Sciences Descriptors (DeCS): “Bone Marrow Transplantation” and “Acute Myeloid Leukemia”. As inclusion criteria: articles available online, in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. Results: From the initial search with the defined descriptors and Boolean operator, 12 studies were found in the selected database and after applying the inclusion and exclusion criteria, 06 studies were selected to compose the review. Final Considerations: Studies indicate that bone marrow transplantation proves to be the most effective treatment for acute myelogenous leukemia due to the low incidence of recurrence. However, it is a complex treatment to be implemented due to the high mortality rates during the process and the scarcity of donors available at REDOME. Even so, more studies on the subject and the elaboration of booklets to raise awareness of the population in being donors are necessary.